ADVANTAGES OF TRANSITION TO INTERNATIONAL STANDARDS OF FINANCIAL REPORTING - Boboyeva Shoira Shoniyozovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In today’s globally integrated economy, transitioning to International Financial Reporting Standards (IFRS) is essential for Uzbekistan’s financial sector. This article discusses the importance and benefits of adopting these standards, drawing on international experiences to highlight how aligning national accounting systems with IFRS can improve financial reporting. The advantages include enhanced transparency, economic efficiency, and an improved investment environment.